The NEET and Hikikomori spectrum: Assessing the risks and consequences of becoming culturally marginalized - Uchida, Yukiko; Norasakkunkit, Vinai (Frontiers in Psychology, 2015)
An increasing number of young people are becoming socially and economically marginalized in Japan under economic stagnation and pressures to be more globally competitive as a post-industrial economy. The phenomena of NEET / Hikikomori (social withdrawal) have attracted global attention in recent years. Though the behavioral symptoms of NEET and Hikikomori can be differentiated, some commonalities in psychological features can be found. Specifically, we believe that both NEET and Hikikomori show psychological tendencies that deviate from those governed by mainstream cultural attitudes, values, and behaviors with the difference between NEET and Hikikomori being largely a matter of degree. In this study, we developed a NEET-Hikikomori risk factors (NHR) Scale that treats NEET / Hikikomori not as a set of distinct diagnoses but as a spectrum of psychological tendencies associated with the risk of being marginalized in society. Based on this idea, we identified three related risk factors in our NHR Spectrum scale: 1) Freeter lifestyle preference¬¬, which in Japan refers to the tendency of consciously choosing not to work despite job availabilities ―, 2) a lack of self-competence, and 3) having unclear ambitions for the future) (Study 1). Study 2 investigated and confirmed the validity of the scale examining NHR differences between occupational groups. The results suggested that NHR is related to psychological tendencies common in the marginalized segments of society. The relationship between these psychological tendencies and actually becoming marginalized across cultures is discussed.